Teoretyczne ujęcia i egzemplifikacje wykluczenia społecznego - Oliwa-Ciesielska, Monika (Humaniora. Czasopismo Internetowe, 2020)
The article presents problems with the theoretical distinction between social exclusion and marginalization, pointing to the proposals of contemporary approaches and references to ambiguously used and abused constructs. The key is to point out that exclusion and marginalization are not a separate problem, but always conditioned by specific social problems, dysfunctions and deficiencies. A separate feature is the separable nature of the highlighted problems, because in social life they are often mutually conditioning areas, which in the case of the occurrence of broadly understood dysfunctions, focus on various severities. The analysis of marginalization and exclusion also shows the problem of building boundaries between these two concepts but also those suppressing excessive inclusion of concepts. The problems contained in the article indicate that researchers are trying to characterize these concepts separately for the purposes of their own analysis, but in common use there is no unified understanding of the term neither marginalization nor exclusion. The article also shows contemporary references to areas of exclusion, which has lost its legal basis in favor of economic and mental isolation processes.